Chemical ordering and large tunnel magnetoresistance in Co2FeAl/MgAl2O4/Co2FeAl(001) junctions. (15th April 2016) - Scheike, Thomas; Sukegawa, Hiroaki; Inomata, Koichiro; Ohkubo, Tadakatsu; Hono, Kazuhiro; Mitani, Seiji
Abstract: Epitaxial magnetic tunnel junctions (MTJs) with a Co2 FeAl/CoFe (0.5 nm)/MgAl2 O4 /Co2 FeAl(001) structure were fabricated by magnetron sputtering. High-temperature in situ annealing led to a high degree of B2-order in the Co2 FeAl layers and cation order of the MgAl2 O4 barrier. Large tunnel magnetoresistance (TMR) of up to 342% was obtained at room temperature (616% at 4 K), in contrast to the TMR ratio ( %) suppressed by the band-folding effect in Fe/cation-ordered MgAl2 O4 /Fe MTJs. The present study reveals that the high degree of B2-order and the resulting high spin polarization in the Co2 FeAl electrodes enable us to bypass the band-folding problem in spinel barriers.